2021
DOI: 10.1039/d0cp05538g
|View full text |Cite
|
Sign up to set email alerts
|

Nature of the different emissive states and strong exciton–phonon couplings in quasi-two-dimensional perovskites derived from phase-modulated two-photon micro-photoluminescence spectroscopy

Abstract: Phase-modulated two-photon photoluminescence identifies the nature of emissive states of quasi two-dimensional q-MPB and q-CPB perovskites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 63 publications
1
10
0
Order By: Relevance
“…Therefore, it might be worthwhile to propose a modification for the interpretation of Eqn. [6] as follows. A "D" value either much smaller or much larger than 1 is the indication of low recombination rate and high photocatalytic efficiency.…”
Section: Effective Massmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it might be worthwhile to propose a modification for the interpretation of Eqn. [6] as follows. A "D" value either much smaller or much larger than 1 is the indication of low recombination rate and high photocatalytic efficiency.…”
Section: Effective Massmentioning
confidence: 99%
“…Sn 2+ , Pb 2+ , Mn 2+ or Ge 2+ ) and X is a halogen (e.g. Cl, Br or I), have gained significant research focus over the past few years due to their promising optoelectronic applications, including semiconducting thin-film transistors, [1,2] light-emitting diodes (LED), [3][4][5][6] solar cells, [7][8][9][10] photodetectors [11,12] and photovoltaics. [13][14][15] Recently, a good number of all-inorganic metal halide perovskites (MHPs), especially cesium (Cs) based perovskites, CsBX 3 have gained a particular attraction due to their fascinating thermal stability [16] as well as intriguing optoelectronic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Metal halide perovskites (MHP), in particular the trihalide perovskites, are a remarkable class of materials that have resulted in a rapid series of breakthroughs in the field of optoelectronic devices. [1][2][3][4][5][6] Over the past decades the MHPs have emerged as suitable materials for solar cells, light emitting diodes, lasers, transistors, and memory devices. [7][8][9][10][11][12][13] It has been demonstrated that MHP-based photovoltaic devices show power conversion efficiencies of more than 22%, [14,15] and the devices can be produced on cheap non-crystalline substrates by both vapor deposition and solution processing.…”
Section: Introductionmentioning
confidence: 99%
“…17 − 21 Notable success has been achieved in regulating the optoelectronic properties through the phase transition process by adjusting the temperature. 21 24 Previous reports have shown that (RNH 3 ) 2 PbX 4 , as a series of single-layer ( n = 1) perovskites, exhibits a reversible phase transition when the temperature decreases. 25 − 27 Whittaker-Brooks and co-workers observed an abrupt phase transition at ∼250 K in an ( n -C 4 H 9 NH 3 ) 2 PbI 4 thin film, and its band energy increased from 2.4 eV at room temperature (RT) to 2.53 eV at low temperature (LT) at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…Another attractive feature of 2D perovskites is their tunable optical properties with the change of environmental conditions. Notable success has been achieved in regulating the optoelectronic properties through the phase transition process by adjusting the temperature. Previous reports have shown that (RNH 3 ) 2 PbX 4 , as a series of single-layer ( n = 1) perovskites, exhibits a reversible phase transition when the temperature decreases. Whittaker-Brooks and co-workers observed an abrupt phase transition at ∼250 K in an ( n -C 4 H 9 NH 3 ) 2 PbI 4 thin film, and its band energy increased from 2.4 eV at room temperature (RT) to 2.53 eV at low temperature (LT) at the same time . Nag and co-workers compared the phase transition in single crystals (SCs) and exfoliated few-layer lattices of the same compound and found that their phase transitions display different hysteresis behaviors during heating/cooling cycles.…”
Section: Introductionmentioning
confidence: 99%